Sheep production in the humid zone of West Africa. I. Reproductive performance in improved production systems in Cote d'Ivoire - Armbruster, T.; Peters, Kurt J.; Hadji-Thomas, A.; Lamizana, P. (Wiley, 1991)
Presents the results of an investigation on 24 improved Djallonke sheep flocks in south-east Cote d'Ivoire concerning the identification of reproductive efficiency of this sheep breed and the analysis of factors influencing performance and of important husbandry techniques to improve sheep production in the humid zone of West Africa.